The role of power morcellation in minimally invasive gynecologic surgery - Boudová, Barbora; Richtárová, Adéla; Frühauf, Filip; Fischerová, Daniela; Mára, Michal (Ceska gynekologie, 2022)
OBJECTIVE: To summarize recent data and knowledge of laparoscopic power morcellation. METHODS: Review of articles. RESULTS: Laparoscopic morcellation has been introduced to gynecologic surgery in 90s. In 2014, Food and Drug Administration announced negative statement about the morcellation use due to the risk of potential spreading of malignant tumor cells. This statement reduced utilization of morcellation, especially in the United States. Since that, many health institutions and organizations started new researches focused on the safety of this surgical technique. After a couple of years, the morcellation is considered as a useful tool if certain rules are followed. CONCLUSION: Morcellation has a place in laparoscopic operative procedures even in 2022, in condition of correct selection of patients and possible utilization of contained in-bag morcellation.
Keywords: morcelace; nádory dělohy; Spojené státy americké; myomectomy; Humans; laparoskopie; Uterine Myomectomy; Female; Leiomyoma; myomektomie; leiomyom; lidé; United States; morcellation; Uterine Neoplasms; laparoscopy; ženské pohlaví; hysterektomie; Laparoscopy; Hysterectomy; Morcellation